A AMC substrate backed gain enhanced multi-band wearable yagi antenna - Chandran K.; Samantaray D.; Mohamed A.; Saha C.; Bhattacharyya S. (My University, 2025)
This paper proposes a modified Yagi-Uda antenna with multiple bands and increased gain for wearable applications. The proposed design consists of a coplanar fed microstrip Yagi antenna backed by an AMC substrate and a ground plane which shows an effective triple operational bandwidth. The AMC is designed to operate at triple bands of 3.4 GHz, 7.1 GHz and 9.5 GHz and the performance comparisons are carried out with and without using AMC substrate. The AMC layer comprises 2 ×3 unit cells to form the back plane reflector for Yagi antenna. The proposed antenna exhibits 2.6%, 2.5% and 5.42% low impedance bandwidths at 3.84 GHz, 4.31 GHz and 6.02 GHz frequency regions, respectively. The overall gain enhancement of about 5 dBi is achieved and shows endfire characteristics. The proposed antenna with high gain is a potential candidate for RFID, defence and, several medical applications. © 2019 IEEE.